Minimally invasive maxillofacial surgery - Troulis, Maria J. (People's Medical Pub. House, USA, 2013)
Features a comprehensive chapter on anatomy as well as thorough coverage of all complications. This book is the first to address minimally invasive reconstruction techniques for the oral/maxillofacial regions.